1998
DOI: 10.1063/1.477632
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra and calculated vibrational frequencies of size-selected C16, C18, and C20 clusters

Abstract: The surface plasmon polariton-enhanced Raman spectra of size-selected C 16 , C 18 , and C 20 clusters isolated in nitrogen matrices are presented along with the calculated vibrational frequencies for the ring and linear chain isomers. The Raman spectra, recorded at a range of excitation wavelengths from 457.9 to 670 nm, show strong resonance enhancement for the three clusters. The calculated vibrational frequencies for ring and linear chain isomers and the cage and bowl structures for C 20 are compared to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 43 publications
(49 reference statements)
3
74
0
Order By: Relevance
“…22,[27][28][29] Fullerenes are graphitic hollow-cage structures incorporating exactly 12 pentagons without restriction of the number of hexagon. Among the fullerene cages, C 60 has the icosahedral cage structure with each pentagons surrounded by five hexagons and is therefore highly aromatic and remarkably stable; in contrast, C 20 fullerene cage ͑see Fig. 1͒ consists of solely 12 pentagonal rings that form a dodecahedron with no hexagons incorporated, resulting in an extreme curvature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…22,[27][28][29] Fullerenes are graphitic hollow-cage structures incorporating exactly 12 pentagons without restriction of the number of hexagon. Among the fullerene cages, C 60 has the icosahedral cage structure with each pentagons surrounded by five hexagons and is therefore highly aromatic and remarkably stable; in contrast, C 20 fullerene cage ͑see Fig. 1͒ consists of solely 12 pentagonal rings that form a dodecahedron with no hexagons incorporated, resulting in an extreme curvature.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] The studies can be traced back to the discovery 23 of the fullerene structure of C 60 , and, thereafter, of their novel properties such as high temperature superconductivity. [24][25][26] Besides the best known "bucky ball" C 60 , a wide range of fullerenes with "magic numbers" has been predicted theoretically and observed experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement with the experiment is rather good and no systematic deviation is observed. Moreover, the comparison between experiment and theory, with some controversies, were reported for Raman spectra for C 16 ; C 18 and C 20 [29]. DensityFunctional calculations of carbon clusters C 2n , n ¼ 2-16, were presented recently [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…There have been many theoretical studies on the vibrational and electronic properties of the C 20 cluster. 9,10 First principle studies of the condensed phases of C 20 cages suggested they might be possible superconductor with high transition temperature (T c ). 11 Experimentally, ''C 20 -type'' film was synthesized by deposition of low-energy carbon clusters with a size distribution centered around C 20 -C 32 .…”
Section: Introductionmentioning
confidence: 99%